2021
DOI: 10.1007/s11906-021-01142-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nutritional Epigenetics in Essential Hypertension: Targeting microRNAs in the Gut-Liver Axis

Abstract: Purpose of Review To review the current knowledge on interactions between dietary factors and microRNAs (miRNAs) in essential hypertension (EH) pathogenesis. Recent Findings There exists an integration of maintenance signals generated by genetic, epigenetic, immune, and environmental (e.g., dietary) factors that work to sustain balance in the gut-liver axis. It is well established that an imbalance in this complex, intertwined system substantially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 161 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Based on recent evidence, nutrients disturb miRNA expressions that could potentially contribute to the pathogenesis of hypertension. 7 Emerging evidence suggests that DME and its active compounds modified miRNA signatures during vascular dementia. 25,33 Previous studies also reported that compounds tannins and rosmarinic acid modulate miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on recent evidence, nutrients disturb miRNA expressions that could potentially contribute to the pathogenesis of hypertension. 7 Emerging evidence suggests that DME and its active compounds modified miRNA signatures during vascular dementia. 25,33 Previous studies also reported that compounds tannins and rosmarinic acid modulate miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…4 In recent years, several studies also indicated that the miRNA-microbiome interaction played a key role in the adjustment of blood pressure. [5][6][7] These previous studies mainly focused on miRNAs (eg, miR-21, miR-122, and miR-129) and gut microbes (eg, Firmicutes/Bacteroidetes ratio). It is well known that fecal samples contain abundant miRNAs.…”
Section: Introductionmentioning
confidence: 99%